Analysis of Customer Satisfaction on Service Quality of KRL Bogor-Jakarta - Muhammad Isradi; Lensi Oktavia Stini; Widodo Budi Dermawan; Amar Mufhidin; Joewono Prasetijo (IJTI International Journal of Transportation and Infrastructure eISSN 2597-4769 pISSN 2597-4734)
Bogor is an area that has the potential for economic growth and development, services and transportation. Bogor is a buffer area for the city of Jakarta, this has an impact on the growing need for transportation service providers to be used as a means of mobilization. Train is one type of mass transportation that is efficient and effective. The advantages of rail transportation are large capacity, relatively low cost, and fast time. The method used is to use a questionnaire that is distributed to passengers of the electric railroad transportation of the Bogor-Jakarta route. The data obtained were then processed using Ms. Excel and SPSS software for statistical testing. The results of the study show that the service quality attributes that are considered the most important by consumers of the Bogor-Jakarta KRL transportation are information, insurance, affordable ticket prices, and cleanliness of toilets at stations. The results of IPA are attributes that are considered important but their low performance is the accuracy of travel schedules, information, assistance in using tickets, speed and accuracy of responding to consumer problems, safety and comfort, insurance, toilet cleanliness. Meanwhile, the attributes that are declared important and good performance are the availability of information related to KRL schedules, friendliness and courtesy of officers, honesty and patience of officers, and ticket prices. The CSI result is known to be 71,241%, which means that consumers are "satisfied" with the Bogor - Jakarta KRL transportation service. The results of the Chi Square KRL Bogor-Jakarta test are gender, age, occupation, income, destination education, transportation to the station, frequency and days of use.